Association of virulence gene expression with colistin-resistance in Acinetobacter baumannii: analysis of genotype, antimicrobial susceptibility, and biofilm formation - Abbas Bahador; Zahra Farshadzadeh; Reza Raoofian; Masoumeh Mokhtaran; Babak Pourakbari; Maryam Pourhajibagher; Farhad B. Hashemi (BMC, 2018)
Abstract Background Acinetobacter baumannii causes difficult-to-treat nosocomial infections, which often lead to morbidity due to the development of antimicrobial drug resistance and expression of virulence genes. Data regarding the association of resistance to colistin, a last treatment option, and the virulence gene expression of A. baumannii is scarce. Methods We evaluated the MLVA genotype, antimicrobial resistance, and biofilm formation of 100 A. baumannii isolates from burn patients, and further compared the in vitro and in vivo expression of four virulence genes among five colistin-resistant A. baumannii (Cst-R-AB) isolates. Five Cst-R-AB isolates were tested; one from the present study, and four isolated previously. Results Our results showed that reduced expression of recA, along with increased in vivo expression of lpsB, dnaK, and blsA; are associated with colistin resistance among Cst-R-AB isolates. Differences in virulence gene expressions among Cst-R-AB isolates, may in part explain common discrepant in vitro vs. in vivo susceptibility data during treatment of infections caused by Cst-R-AB. Conclusions Our findings highlight the intricate relationship between colistin-resistance and virulence among A. baumannii isolates, and underscore the importance of examining the interactions between virulence and antimicrobial resistance toward efforts to control the spread of multidrug-resistant A. baumannii (MDR-AB) isolates, and also to reduce disease severity in burn patients with MDR-AB infection.